2005
DOI: 10.1080/13504850500190097
|View full text |Cite
|
Sign up to set email alerts
|

Political elections and foreign investor trading in South Korea's financial markets

Abstract: This article investigates the relationship between foreign investors' trading behaviour and political election events in South Korea and the effect of the relationship on the financial markets via a bivariate GARCH (1,1) model analysis. The empirical results show that the KOSPI 200 index return (total trading volumes of spot) and the derivatives volume have a negative (positive) relationship for foreign investors. South Korea shifted to a free floating exchange rate system, however, it did not have an effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Political events within a country as well as its external political relations influence the level of stock market returns. Chiu, Chen and Tang (2005) show that foreign investors' reactions to the electioneering events in South Korea showed significant impact on the stock market. Political events have a strong significant association with the volume of trading activities and market returns (Frey & Waldenstrom, 2004;Bailey, Heck & Wilkens, 2005;Aktas & Oncu, 2006;Beaulieu, Cosset, & Essaddam, 2006).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Political events within a country as well as its external political relations influence the level of stock market returns. Chiu, Chen and Tang (2005) show that foreign investors' reactions to the electioneering events in South Korea showed significant impact on the stock market. Political events have a strong significant association with the volume of trading activities and market returns (Frey & Waldenstrom, 2004;Bailey, Heck & Wilkens, 2005;Aktas & Oncu, 2006;Beaulieu, Cosset, & Essaddam, 2006).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Jorion and Geotzmann (1999) derived that political events had an interruption in the market transactions. Chiu et al (2005) proved that political elections in South Korea changed the behavior of foreign investors in financial markets. Beaulieu et al (2006), Aktas and Oncu (2006), Bailey et al (2005) and Frey and Waldenstrom (2004) argued that political events had a strong effect on the returns and trading volume of the financial markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded that the whole market and the overall industry did not show any significant response to all events. Chiu et al (2005) studied the behavior of foreign investors in the four elections of South Korea. The results showed that negative relationship exists between KOSPI 200 index return and the volume of both future and option contracts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other researches have tracked financial market performance in relation to elections (Easaw and Garratt, 2000;Steeley, 2003;Bru¨ggelambert, 2004;Chiu et al, 2005). During election campaigns, the political parties provide economic policies that are acceptable to voters, and competition among parties generally promotes economic development (Pantzalis et al, 2000).…”
Section: Introductionmentioning
confidence: 99%